2009
DOI: 10.1111/j.1464-410x.2009.08624.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bony pelvic dimensions measured by preoperative magnetic resonance imaging on performing robot‐assisted laparoscopic prostatectomy

Abstract: dimensions measured by preoperative MRI, with operative duration, estimated blood loss (EBL), surgical margin status, and postoperative urinary continence and erectile function. RESULTSFor operative duration, no pelvic dimension had a significant association on univariate analysis, with only the newly developed variable of pelvic cavity index approaching significance ( P = 0.071). Only prostate volume had a significant association with operative duration on multivariate analysis ( P = 0.015). For EBL, no bony … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 25 publications
4
34
0
Order By: Relevance
“…Hong et al, using anatomical parameters obtained from MRI, reported that the working space for robotic arms in the pelvic cavity can be estimated using the PCI. 4 Although no other pelvic dimensions, including the PCI, were found to be associated with operative duration in their study, Mason et al reported that a higher PV-to-PCI ratio was associated with a longer operative time and higher EBL, suggesting that patients with deeper pelvises and larger prostates would be predicted to have more difficulty in RARP procedures. 5 Our analyses also showed that the PV-to-PCI ratio was a significant predictor of console time and EBL using linear regression analysis.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…Hong et al, using anatomical parameters obtained from MRI, reported that the working space for robotic arms in the pelvic cavity can be estimated using the PCI. 4 Although no other pelvic dimensions, including the PCI, were found to be associated with operative duration in their study, Mason et al reported that a higher PV-to-PCI ratio was associated with a longer operative time and higher EBL, suggesting that patients with deeper pelvises and larger prostates would be predicted to have more difficulty in RARP procedures. 5 Our analyses also showed that the PV-to-PCI ratio was a significant predictor of console time and EBL using linear regression analysis.…”
Section: Discussionmentioning
confidence: 72%
“…In particular, the PCI represents the working space for the robotic arms within the pelvic cavity. 4 We also measured the PTD, PAD and PCD, which we used to calculate PV using the ellipsoid formula:…”
Section: Mri Measurementsmentioning
confidence: 99%
See 3 more Smart Citations